2012
DOI: 10.5688/ajpe76469
|View full text |Cite
|
Sign up to set email alerts
|

Use of Online Modules to Enhance Knowledge and Skills Application During an Introductory Pharmacy Practice Experience

Abstract: Objectives. To implement and assess the effectiveness of online instructional modules to increase the consistency of learning outcomes related to students' patient-care practice knowledge and their skills application and confidence across introductory pharmacy practice experience (IPPE) sites. Design. Twenty online modules were created to provide uniform delivery of instructional content that complemented classroom instruction and to introduce students to common pharmacy-practice skills in the patient-care are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…Of 11 studies assessing knowledge change, all reported a significant improvement in knowledge immediately after e-learning. [30][31][32]34,35,38,39,[41][42][43]46 However, the magnitude of the gain varied considerably from study to study (range 7% to 46%). Comparative studies assessing knowledge change demonstrated e-learning to be equivalent to lecture-based learning and superior to no training.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 11 studies assessing knowledge change, all reported a significant improvement in knowledge immediately after e-learning. [30][31][32]34,35,38,39,[41][42][43]46 However, the magnitude of the gain varied considerably from study to study (range 7% to 46%). Comparative studies assessing knowledge change demonstrated e-learning to be equivalent to lecture-based learning and superior to no training.…”
Section: Resultsmentioning
confidence: 99%
“…Every study assessed a different learning topic, although 3 studies included diabetes within their focus. [30][31][32] Six studies (35%) assessed effectiveness of e-learning in pharmacists; [32][33][34][35][36][37] 10 studies (59%) assessed pharmacy students (of which 1 included preregistration pharmacists), 31,[38][39][40][41][42][43][44][45][46] and 1 study assessed both pharmacists and pharmacy students. 30 The number of participants in each study ranged from .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 After utilizing the web-based learning modules, students' postintervention scores showed significant improvement in clinical knowledge, skill application, and confidence for the IPPE. Similar to results of our study, students in the Ruehter et al study reported positive perceptions of this educational intervention in preparing them for the clinical experiences.…”
Section: 2mentioning
confidence: 99%
“…This can include the use of different levels of learners, team-based precepting, and outside preparation. [6][7][8][9][10][11][12] Use of web-based learning is one mechanism available to standardize knowledge of key clinical disease states across multiple learning experiences. Web-based learning also provides the ability to assess knowledge prior to the APPE.…”
Section: Introductionmentioning
confidence: 99%